Entrepreneurship Education and Perceived Economic Opportunities as Determinants of Students’ Entrepreneurial Decisions: The Mediating Role of Risk-Taking Behavior - Sutrisno; Abu Muna Almaududi Ausat; Syamsuri; Susatyo Adhi Pramono; Hizbul Khootimah Azzaakiyyah; Muhammad Aqib Shafiq (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to examine the influence of entrepreneurship education and perceived economic opportunities on students’ entrepreneurial decisions through risk-taking behavior as a mediating variable. This research integrates the Theory of Planned Behavior (TPB) and Behavioral Finance Theory (BFT) to explain how knowledge, opportunity perception, and psychological attitudes toward risk shape entrepreneurial decision-making among students. A quantitative approach was employed using a structured questionnaire distributed to university students in Semarang City who had participated in entrepreneurship courses. A total of 104 valid responses were analyzed using SEM-PLS, with respondents selected through a purposive sampling technique based on specific research criteria. The results indicate that entrepreneurship education and perceived economic opportunities have positive and significant effects on students’ risk-taking behavior. Furthermore, risk-taking behavior significantly influences students’ entrepreneurial decisions. The analysis also confirms that risk-taking behavior partially mediates the relationship between entrepreneurship education, perceived economic opportunities, and students’ entrepreneurial decisions. These findings highlight that entrepreneurial decisions among students are influenced not only by entrepreneurial knowledge and opportunity recognition but also by psychological readiness to take risks in uncertain economic conditions.